Putting Students First MnSCU's Plan for Minnesota, 1997-2000. - Minnesota State Colleges and Universities System, St. Paul.; Minnesota State Colleges and Universities System, St. Paul. ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
Focusing on the role of Minnesota's State Colleges and Universities (MnSCU) in meeting the economic and educational needs of Minnesota, this plan describes the mission and strategic goals of the system for 1997to 2000. Following introductory materials, the history of the MnSCU system is discussed, highlighting its formation in 1995 as a merger of 10 technical colleges, 8 community colleges, 11 consolidated colleges, and 7 state universities. Responsibilities to the state of Minnesota are then described and the MnSCU mission statement is presented. Next, external considerations for strategic planning are reviewed, including a demographic and economic profile of Minnesota, a profile of state educational needs, and descriptions of external threats and opportunities. Internal considerations for strategic planning are then discussed, including profiles of state finances and students as of fiscal year 1996, internal strengths and weaknesses, and threats and opportunities. Following responses from town meetings held in 1996 and the MnSCU values and visions statements, the following six strategic goals are presented: (1) provide academic accountability by measuring student achievement; (2) ease student mobility between institutions through skill-based transfer; (3) restructure career education to ensure that students receive general education as well as technical competencies; (4) make electronic education a core element of the MnSCU; (5) align programs and services with community and business needs; and (6) strengthen partnerships with K-12 institutions. Concluding remarks address methods for financing the plan. A planning timeline, the MnSCU town meeting schedule, student profile data, and a map of campus locations are appended. (HAA)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Planning; Community Colleges; Economic Research; Educational Finance; Higher Education; Institutional Advancement; Institutional Mission; Mission Statements; Organizational Objectives; Statewide Planning; Strategic Planning; Student Characteristics; Two Year Colleges; Minnesota State Colleges and Universities; Reports, Descriptive